THE MODERN VIEW OF THE FORMATION OF READINESS OF THE FUTURE FITNESS TRAINERS TO PROFESSIONAL WORK - Anastasiya Prіma (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The deep socio-economic changes in Ukraine, the rapid development of the fitness industry and the ever-growing need for professional athletic personnel resulted in the need for fitness trainers who are able to use effective means of improvement of the nation in order to improve its level and the introduction to a healthier lifestyle. At present, the leading areas in the field of physical culture and sports development of higher education are: training, competitiveness on the labor market, competecet and mobility in the field of physical culture and sports; the development of new standards for training of future specialists; improving the content of the higher pedagogical education in accordance with modern requirements for the level of professional competence of future professionals; development and testing of innovative technologies of physical training and the inclusion of the most effective ones for the content of higher education in the field of physical culture and sports; implementation of continuous interaction with educational authorities, general educational institutions and youth schools in order to develop a unified strategy for the practical implementation of the new educational paradigm; development, testing and implementation of innovative forms and methods of organization of extracurricular sports and recreation activities. Modernization of the higher sports education should be paramount, and continuous, to respond flexibly to all the processes  which occur in the sphere of physical culture and sports. The goal of the modernization of professional training of future specialists in physical education and sport is to create a sustainable development mechanism of such educational system that meets the needs of society, the state and the individual, and can significantly improve the quality of higher education sports, socio-cultural and health formative role of physical culture.